STANDARDIZATION AND CYTOTOXIC POTENTIAL OF A POLY HERBAL FORMULATION- CHATHURMUKA CHOORANAM - REVATHI.S; SARASWATHI.U; POORNI K.E (International Journal of Pharma and Bio Sciences, 2014)
Siddha system of medicine is an ancient traditional system intertwined with the mythology and culture of ancient Tamil civilization. The present study investigates the Standardization, Phytochemicals and Cytotoxic potential of a poly herbal siddha formulation Chathurmuka chooranam. Various parameters performed which include organoleptic, physiochemical and flow properties. Its cytotoxicity was determined by MTT assay in Hep G2 cell line. Phytochemicals investigation was also analyzed which revealed the presence of alkaloids, phenols, and flavanoids. The cytotoxicity of the crude extract was found to be very potent against cancer cell line .The results obtained may pave the way for the quality assurance and control organization mostly depends upon the plant drugs as the primary health care needs.